BARRIERS TO PALLIATIVE AND HOSPICE CARE UTILIZATION AMONG OLDER ADULTS WITH CANCER: A SYSTEMATIC REVIEW - Parajuli, J (Innov Aging, 2018)
The number of older adults with cancer is increasing in the United States. However, palliative and hospice care are not optimally utilized by this population. This systematic review aims to identify the barriers to palliative and hospice care utilization in older adults with cancer. Literature searches were conducted using PubMed, CINHAL, Psych-Info, Embase and Cochrane Library databases. The keywords used were (cancer OR neoplasms OR oncology) AND (palliative care OR supportive care OR end of life OR terminal OR dying OR hospice) AND (barriers OR obstacles OR challenges OR difficulties). Eight research articles that examined the barriers to palliative and hospice care were identified and analyzed. PRISMA guidelines were followed for the review. The study designs were heterogeneous, including qualitative, quantitative and mixed methods. Four major barriers to palliative or hospice care were identified including misconceptions and lack of understanding of palliative care and hospice care, lack of accessibility to palliative and hospice care services, communication challenges between patients and healthcare providers, and policy and reimbursement issues. This is a pioneer study to review the barriers to palliative and hospice care utilization with focus on older adults. The findings can be used to guide intervention development to improve the use of palliative and hospice care utilization in this population.